VALUE AT RISK (VAR) METODE DELTA-NORMAL BERDASARKAN DURASI UNTUK UKURAN RISIKO OBLIGASI PEMERINTAH - Setiani Setiani; Di Asih I Maruddani; Dwi Ispriyanti (Jurnal Gaussian, 2021)
A bond is one of invesment instrument that is basically a debt instrument. In investing, beside getting profit there is also the risk of loss. The risk of loss is unavoidable but it can be manageable. The concept of a portfolio in investing is to minimize risk. Value at Risk (VaR) is a method used to measure risk where VaR states the estimated amount of the maximum loss that will be obtained at a certain level of confidence during a certain period in normal market conditions. In this article the risk of bonds FR0053, FR0056, FR0059, FR0061 and portfolio combinations calculated with VaR value of the Delta-Normal method are calculated based on the duration of the bonds. Normality test of the bond market price return is required before calculating VaR. The results obtained if it is assumed that the bonds are purchased at a price of 100 and with a confidence level of 95%, then the portfolio that has the smallest risk is the Bond portfolio of FR0059 and FR0061 with a VaR value  Rp 21,436 (Trillions).